7Li NMR spectra and spin-lattice relaxation in lithium heptagermanate single crystal. Issue 1 (3rd April 2020) - Vogel, M.; Petrov, O.; Trubitsyn, M.; Nesterov, O.; Volnianskii, M.
Abstract: 7 Li NMR spectra and spin-lattice relaxation in Li2 Ge7 O15 single crystal have been analyzed. It is shown that the NMR spectrum consists of quadrupolar triplets from 7 Li ( I  = 3/2) nuclei located in structurally nonequivalent Li(1) and Li(2) sites ( T  = 300 K). On heating the quadrupolar splitting decreases as a result of thermal vibrations of 7 Li quadrupolar axes whereas NMR lines narrow due to translational motion of lithium ions. Measurements of the spin-lattice relaxation rate T1 −1 give information about the time scale and the activation energy of lithium ions motion. The results of NMR studies are compared with findings from electrical conductivity measurements.